The Greek Catholic Church in Czechoslovakia under the pressure of normalisation in 1969 – 1989 - Lukáčova, Jana; Šturák, Peter; Weis, Martin (Journal of Education Culture and Society, 2022)
Aim. This article presents the status of the Greek Catholic Church during a defined period. It brings the functioning of this religion in the period of normalisation of society closer.Methods. Our study is the result of archival and document-based research, as well as expert studies and monographs dealing with the above-mentioned issue.Results. Although we can define the period studied in our research as a period of relative freedom when compared with the years 1950–1967, it cannot be perceived as a total liberation of the Church. Unfortunately, the political reality was also reflected in the life and functioning of the Church itself. The Greek Catholic Church and its leaders understood that without the necessary support from the state and regime, they would lose their freedom mainly attained in the first half of 1968.Conclusion. The Greek Catholic Church had to face several important and ground-breaking tasks that were to ensure its stability for functioning and administration after 18 years of its non-existence. This involved receiving state consent for Consecrator ThDr. Basil (Vasiľ) Hopko, leadership of the Greek Catholic Church in general, consolidation of relationships and conflict resolution between the Greek Catholic Church and the Orthodox Church, or even the area of support and consent for building its own institute of theological formation.